Efficiency of the treatment of epilepsy in adolescent children according to indicators of evoked potentials - Gekova, M.; Tantsura, L. (Journal of Education, Health and Sport, 2023)
The aim: to identify the peculiarities of the indicators of evoked potentials in epileptic children against the background of anticonvulsant treatment. Methods: auditory long-latency, visual flash-evoked potentials. Epileptic children were divided into two groups. The first group received monotherapy, the second group received polytherapy. Results: The study of average values of latencies showed that children with polytherapy had a more pronounced lengthening of latencies compared to those of the first group. According to the latencies analysis in the group of monotherapeutic children there were no ties between various anticonvulsant drugs and results of examination. There was a tendency towards normalization of latencies, mainly for visual evoked potentials in the group of children with a positive response to treatment. Conclusion: It is advisable to use the method of evoked potentials to assess the functional state of sensory systems in children with epilepsy, in order to predict the course of the disease and assess the effectiveness of treatment.